New Years Eve celebration
Family group portrait on New Years Eve, at 780 Irene Street, San Jose. Standing from left to right: Teresa Massa Carozza, Louise Massa Albanese, Rosie Albanese Romanello, and Christine Albanese McArthur. Sitting from left to right: Steve McArthur and Lad, Flora Albanese Talesfore, Rose Carozza Gordon, Marvin McArthur, Vera Antuzzi Lema, and Joe Lema.